Resource assessment and projections for the belugas off West Greenland using the population model of HITTER-FITTER - Butterworth, Doug S; Plagányi, Éva E; Geromont, Helena F (NAMMCO Scientific Publications, 2002)
The population model of the HITTER-FITTER package is applied to compute trajectories for single and two stock scenarios for the beluga population wintering off West Greenland. Values of MSYR1+ from 1% to 4% are considered, with results computed to hit best estimates and lower 5%-iles for total abundance in 1999. Twenty year projections show that even for the most optimistic of these options in the single stock case, the resource is rendered extinct within 20 years if recent estimated annual catch levels of some 700 are continued. A time series of relative abundance information from surveys indicates that MSYR1+ may be no more than 0.5%. All scenarios considered are suggestive of a heavily depleted resource for which catch levels need to be substantially reduced to secure against possible further reduction of the population.